Updating understanding of real-world adverse events associated with omeprazole. - Jijun Zhang; Jie An (PLoS ONE)
This study aims to assess the adverse events (AEs) and safety profile of omeprazole, a widely used proton pump inhibitor (PPI) for acid-related diseases. Despite being a first-line treatment, its overuse due to easy accessibility and lack of public awareness about usage guidelines may lead to potential side effects, necessitating a reassessment of its safety. We extracted 119,159 adverse event reports (AERs) related to omeprazole from the FDA Adverse Event Reporting System (FAERS) database, covering data from Q1 2004 to Q4 2023. A disproportionality analysis was performed to evaluate indications, concomitant medication use, and safety. Omeprazole was commonly prescribed for gastroesophageal reflux disease (GERD), dyspepsia, peptic ulcers, and gastritis. It was frequently used with drugs like aspirin, lisinopril, furosemide, atorvastatin, and metoprolol. Notably, renal and urinary disorders showed strong positive signals, including chronic kidney disease, acute kidney injury, and renal failure, with statistically significant disproportionality measures. The study also identified adverse reactions not listed on drug labels, such as hyperparathyroidism secondary and intentional product misuse. Our findings provide new insights into the safety of omeprazole in real-world clinical settings, highlighting novel adverse events and offering evidence for safer clinical use.